Problems safety of living a man-solution, perspectives - Rusanova, L. D.; Berezutskyi, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2017)
This thesis examines problems safety of living a man. Scientists explore many questions connected with the safety of living. This topic is also important concerning working conditions of the person. The main thing which everyone should know is following the rules of safety of living to make the working and home conditions safe. The science about safety of living is very interesting and perspective. Future stays after it.

У статті розглядаються проблеми безпеки життя людини. Учені вивчають багато питань, пов'язаних з безпекою життя. Ця тема також важлива щодо умов трудової діяльності людини. Головне, що кожен повинен дотримуватись правил безпеки життя, щоб зробити робочі та домашні умови безпечними. Наука про безпеку життя дуже цікава і перспективна. Майбутнє залишається за нею.
Keywords: person; problem; solution; perspective; threats; classification; безпека життя; особистість; проблема; рішення; перспектива